2022
DOI: 10.1021/acs.energyfuels.2c03544
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the CO2 Effective Distance and CO2-EOR Storage for Tight Oil Reservoir

Abstract: CO 2 underground storage is an important approach to reduce carbon emissions; meanwhile, the combination of CO 2 storage and economic benefits can further promote the long-term development of carbon neutrality. Global tight oil reserves are abundant, but the depletion development of most tight reservoirs is unsatisfactory. Therefore, it is crucial to utilize CO 2 storage combined with enhanced oil recovery (EOR) for tight reservoir development. At present, there are few experimental studies on the CO 2 effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Henry’s constant is the amount of gas dissolved in a unit volume of liquid. , As the Henry constant increases, the cumulative oil production, crude oil recovery rate, and CO 2 oil change rate all slowly increase. However, the CO 2 burial capacity and burial rate decrease.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Henry’s constant is the amount of gas dissolved in a unit volume of liquid. , As the Henry constant increases, the cumulative oil production, crude oil recovery rate, and CO 2 oil change rate all slowly increase. However, the CO 2 burial capacity and burial rate decrease.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Global climate change has attracted widespread attention from the international community, and reducing greenhouse gas CO 2 emissions to address the challenges of climate change has gradually become a consensus in the international community. Coal, oil, and natural gas account for 70% of the total primary energy consumption, but they produce 2/3 of CO 2 , the main source of greenhouse gases. From 1750 to 2020, the volume fraction of CO 2 in the global atmosphere increased from 277 to 416 ppm, an increase of 1.5 times. The Paris Climate Agreement determined that by 2050, the global average temperature increase needs to be controlled within 2 °C before industrialization and strive to be within 1.5 °C . Research has shown that carbon capture, utilization, and storage technology (CCUS) effectively mitigates global climate change.…”
Section: Introductionmentioning
confidence: 99%
“…The first diffusion stage refers to the process in which CO 2 diffusion front does not reach the interface between two oil phases, and CO 2 6) There is no mixing, and components exchange between the light oil and the heavy oil. (7) The swelling of the oil phases is considered, but the swelling of the water phase is neglected.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Global warming and insufficient energy supply have aroused interest in enhanced oil recovery (EOR) with CO 2 and CO 2 capture, utilization and storage (CCUS). Injection of CO 2 into oil reservoirs known as CO 2 -enhanced oil recovery (EOR) can not only help to store the CO 2 but also improve the recovery of crude oil. Hence, this process is considered to be the most cost-effective CCUS technique and has been widely used in the development of oilfields. , In CO 2 injection EOR projects, CO 2 diffuses into the formation and helps improve oil recovery by reducing the crude oil viscosity, supplementing the formation energy, swelling oil volume, and reducing the interfacial tension. , Studies have shown that the in situ mass transfer between CO 2 and heavy oil under reservoir conditions is dominated by molecular diffusion and dispersion. , The magnitude of molecular-diffusion coefficients affects the time for the heavy oil to achieve desirable viscosity reduction and swelling effect, thus influencing the oil-production response. , Therefore, the determination of CO 2 diffusion coefficient has extremely important guidance on CO 2 -EOR risk assessment, engineering design, and economic evaluation. , …”
Section: Introductionmentioning
confidence: 99%
“…Tight rocks have complex pore systems, including micro-and macropores, due to depositional and diagenetic processes. 26 Macropores are voids between detrital grains, which form during the depositional process, while micropores originate before the depositional process and commonly exist between grains and authigenic clay minerals. 27 Compaction, the presence of quartz overgrowth, and small grain size can reduce the contribution of macropores in tight sandstones.…”
Section: Introductionmentioning
confidence: 99%